What students write about when students write about mechanisms: analysis of features present in students' written descriptions of an organic reaction mechanism. Issue 4 (10th July 2020) - Watts, Field M.; Schmidt-McCormack, Jennifer A.; Wilhelm, Catherine A.; Karlin, Ashley; Sattar, Atia; Thompson, Barry C.; Gere, Anne Ruggles; Shultz, Ginger V.
Abstract : Learning to reason through organic reaction mechanisms is challenging for students because of the volume of reactions covered in introductory organic chemistry and the complexity of conceptual knowledge and reasoning skills required to develop meaningful understanding. However, understanding reaction mechanisms is valuable for students because they are useful for predicting and explaining reaction outcomes. To identify the features students find pertinent when explaining reaction mechanisms, we have collected students' written descriptions of an acid-catalysed amide hydrolysis reaction. Students' writing was produced during the implementation of Writing-to-Learn assignments in a second semester organic chemistry laboratory course. We analysed students' written responses using an analytical framework for recognizing students' mechanistic reasoning, originally developed with attention to the philosophy of science literature. The analysis sought to identify the presence of specific features necessary for mechanistic reasoning belonging to four broad categories: (1) describing an overview of the reaction, (2) detailing the setup conditions required for the mechanism to occur, (3) describing the changes that take place over the course of the mechanism, and (4) identifying the properties of reacting species. This work provides a qualitative description of the variety of ways in which students included these features necessary for mechanistic reasoning in their writing. We additionally analysed instances of co-occurrence for these features in students' writing to make inferences about students' mechanistic reasoning, defined here as the use of chemical properties to justify how electrons, atoms, and molecules are reorganized over the course of a reaction. Feature co-occurrences were quantified using the lift metric to measure the degree of their mutual dependence. The quantitative lift results provide empirical support for the hierarchical nature of students' mechanistic descriptions and indicate the variation in students' descriptions of mechanistic change in conjunction with appeals to chemistry concepts. This research applies a framework for identifying the features present in students' written mechanistic descriptions, and illustrates the use of an association metric to make inferences about students' mechanistic reasoning. The findings reveal the capacity of implementing and analysing writing to make inferences about students' mechanistic reasoning.